1993
DOI: 10.1139/v93-173
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of lignin model compounds on solid supports

Abstract: . Can. J. Chem. 71, 1340 (1993).The photochemistry of several substituted a-(aryloxy)acetoveratrones that are models for chromophores in lignin has been studied using a combination of laser flash photolysis and product studies in solution and on silica, Na-X zeolite, and cellulose. The lifetimes of the triplet ketones vary substantially with the electron-donating ability of the substituents in the a-aryloxy ring, with values ranging from 30 ns for the 4-methoxy derivative to 5.5 ps for the 4-cyano ketone in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…The approximate twofold increase in the yield of the ketone 4 upon introduction of oxygen is consistent with a mechanism in which direct reaction with oxygen (reaction [8]) competes with the bimolecular disproportionation of 1' to give one equivalent of 1 and one of 4 (reaction [9]). In the presence of oxygen all of the ketyl radicals are trapped by reaction [8] and subsequently tranformed into 4.…”
Section: Aah0xch3c(h)=ch2+ch3c(oh)=ch) =supporting
confidence: 72%
See 1 more Smart Citation
“…The approximate twofold increase in the yield of the ketone 4 upon introduction of oxygen is consistent with a mechanism in which direct reaction with oxygen (reaction [8]) competes with the bimolecular disproportionation of 1' to give one equivalent of 1 and one of 4 (reaction [9]). In the presence of oxygen all of the ketyl radicals are trapped by reaction [8] and subsequently tranformed into 4.…”
Section: Aah0xch3c(h)=ch2+ch3c(oh)=ch) =supporting
confidence: 72%
“…They proposed that up to 70% of the photogenerated chromophores were generated via path C in which ketyl radicals, generated from P-guaiacoxybenzyl alcohols, underwent fragmentation to give the phenoxyl radical directly and a substituted acetophenone (via the initally formed enol). While the formation and reactivity of phenoxyl radicals in the lignin matrix is not well understood, a number of photochemical studies (5)(6)(7)(8)(9)(10)(11)(12) using model compounds in solution or adsorbed on solid supports have provided some insights into the factors influencing all of the proposed mechanisms. In one of these studies (7) it was suggested that the fragmentation of 1 -phenyl-2-phenoxyethanol-1 -yl radical (1') formed from the reaction of photogenerated tert-butoxyl radicals with 1-phenyl-2-phenoxyethanol (1, eqs. [I], [2]) undergoes rapid fragmentation to yield phenoxyl radical and acetophenone (2, eq.…”
Section: Introductionmentioning
confidence: 99%
“…In this work the rate constant for the fragmentation was estimated from a product study in which the α-phenoxy fragmentation occurred in competition with the loss of halide ion from the acetophenone ring. Thermally and photochemically induced fragmentations of the C−OPh bond in other α-aryloxyacetophenones also have received considerable attention as it is believed that these are important reactions in the degradation of lignin, leading to the photoyellowing of paper. While most of the color reversion is thought to occur via photogenerated aryloxyl radicals, lignin also contains alkoxystilbene substructures which can act as photoreductants. , It is likely that some degradation of the lignin matrix occurs via the α-aryloxyacetophenone radical anions which are formed from a photoinduced electron transfer route in which electron-rich alkoxyl stilbenes are electron donors.…”
Section: Introductionmentioning
confidence: 99%
“…Melting points were determined on an X-4 binocular microscope melting point apparatus (Beijing Tech Instruments, Beijing, China) and were uncorrected. Compounds 4a-h were synthesized by reaction of an α-bromoacetophenone with the corresponding phenol in dry acetone and anhydrous K 2 CO 3 according to the literature, 21 and were recrystallized from ethanol. All reagents are analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…General synthetic procedure for 1-(3,4-dimethoxyphenyl)-2-(substituted phenoxy)ethanone (4a-h). Compounds 4a-h were synthesized by reaction of an a-bromoacetophenone with the corresponding phenol in dry acetone and anhydrous K 2 CO 3 according to the literature, 21 and were recrystallized from ethanol. The data for compounds 4a-h can be found in the ESI.…”
Section: Methodsmentioning
confidence: 99%